Frailty in older adults with chronic heart failure in a hospital from Lima: - Carhuallanqui Bastidas, Jhovana (2021)
Objective. To determine the prevalence of frailty in older adults with heart failure and to examine the association between frailty and socio-demographic and clinical characteristics in patients in the Chronic Heart Failure program of the Guillermo Almenara Irigoyen National Hospital in the period 2018-2020. Materials and methods. Observational, cross-sectional, correlational study with quantitative approach in patients older than 60 years who had a frailty assessment using the Edmonton scale; as non-frail (0-4), apparently vulnerable (5-6), mildly frail (7-8), moderately frail (9-10) and severely frail (11-17). The association of frailty and patient characteristics was assessed using Pearson's Chi-Square test, values of p<0.05. and with a 95% confidence interval were considered significant. Results. The prevalence of frailty was 58.8%, most patients were male (71.8%) and the average age was 72.9 years. Age and number of comorbidities were statistically significant factors associated with frailty with p=0.004 and p<0.001 respectively. Conclusions. The prevalence of frailty was high in patients older than 60 years in the chronic heart failure program. Older patients with more comorbidities were at higher risk of frailty, highlighting the need for comprehensive assessment and screening for frailty in order to design secondary prevention programs in a timely manner.